STUDENTS’ READING COMPREHENSION IN READING ENGLISH TEXTBOOK - Jusman A. Sahmal; Sutaryo Sutaryo; Naniek Jusnita; Suratman Dahlan (Universitas Khairun, 2022)
This research objective is to find out the students’ reading comprehension in reading English textbook at the English Language Education Study Program, University of Khairun. This research used qualitative method with descriptive statistical analysis. The sample of the research consisted of 30 students at the English Language Education Study Program, University of Khairun. The instrument was reading comprehension test to collect the data. The data were analyzed by interpreting the result of reading comprehension test. The result of this research shows that the score of reading comprehension in reading English textbook at The English Language Education Study Program, University of Khairun were categorized as poor with the average of (24.63). The highest score of students’ reading comprehension was poor (53) and the lowest score was also poor (7). Their abilities in Literal (L), Inferential (F), and Critical Creative (K) are also generally poor.